2020
DOI: 10.1080/03007995.2020.1822309
|View full text |Cite
|
Sign up to set email alerts
|

Survival analysis for all-cause revision following primary total hip arthroplasty with a medial collared, triple-tapered primary hip stem versus other implants in real-world settings

Abstract: Survival analysis for all-cause revision following primary total hip arthroplasty with a medial collared, triple-tapered primary hip stem versus other implants in real-world settings, Current Medical Research and Opinion,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…A total of 446 records were excluded by examining their titles and/or abstracts, leaving 40 records for full-text review. Twenty-nine studies were excluded after full-text review: ten because they reported on non-conventional-length (short, long) or non-HA-coated stems ( 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ), eight because they compared collared versus collarless stems with different designs or coatings ( 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ), five because they were letters to the editor, technical notes, or correspondence ( 38 , 39 , 40 , 41 , 42 ), three because they did not report on any outcomes ( 14 , 43 , 44 ), one because it compared hemiarthroplasty versus THA ( 45 ), one because it was a cadaveric study ( 46 ), and one because it was a non-comparative study ( 47 ). A further three articles were excluded because the outcomes of interest were not presented separately for collared versus collarless stems (the authors were contacted at least three times but none responded) ( 4 , 6 , 48 ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 446 records were excluded by examining their titles and/or abstracts, leaving 40 records for full-text review. Twenty-nine studies were excluded after full-text review: ten because they reported on non-conventional-length (short, long) or non-HA-coated stems ( 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ), eight because they compared collared versus collarless stems with different designs or coatings ( 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ), five because they were letters to the editor, technical notes, or correspondence ( 38 , 39 , 40 , 41 , 42 ), three because they did not report on any outcomes ( 14 , 43 , 44 ), one because it compared hemiarthroplasty versus THA ( 45 ), one because it was a cadaveric study ( 46 ), and one because it was a non-comparative study ( 47 ). A further three articles were excluded because the outcomes of interest were not presented separately for collared versus collarless stems (the authors were contacted at least three times but none responded) ( 4 , 6 , 48 ).…”
Section: Resultsmentioning
confidence: 99%
“…Chitnis et al reported on their results using the MCTT stem in 1200 patients, extracted from a retrospective database. They found a lower revision rate at 3 years as compared to conventional hip stems (1.03% vs. 2.63%) [20]. The recent American Joint Replacement Registry (AJRR) data from 2020 also showed that the MCTT stem had the lowest revision rate at three years among all stems analyzed [21].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, cementless stems account for approximately 70% of THA cases [1,[4][5][6][7]. A t and ll type concept (collared and full hydroxyapatite coated) cementless stem (ACTIS stem; Depuy Synthes, Warsaw, IN, USA) has been available since 2016 and used in retrospective studies on THA [8][9][10]. However, there has been no study on BHA using this stem for treatment of femoral neck fractures.…”
Section: Introductionmentioning
confidence: 99%